(untitled) (Research, Society and Development, 2020)
Objective: Identifying national productions in the literature regarding medication errors in Intensive Care Units. Method: It is an integrative review conducted through access to SCIELO and VHL databases using the keywords “Medication errors”, “Adverse event”, “Nursing” and “Adult ICU”. Results: Eight articles highlighting the issue were found. Conclusion: The importance of strengthening strategies to minimize drug-related adverse events. Thus, the relevance of research that highlights the nature of these adverse events is highlighted. Therefore, it is essential to work with strategies to better manage the medication system.